Achieving stable remission with maintenance electroconvulsive therapy in a patient with treatment-resistant schizophrenia: A case report. Issue 48 (December 2017) - Moeller, Sebastian; Kalkwarf, Neele; Lücke, Caroline; Ortiz, Diana; Jahn, Sonja; Först, Christiane; Braun, Niclas; Philipsen, Alexandra; Müller, Helge H.O.
Abstract: Rationale: Up to one third of all schizophrenic patients are classified as having treatment-resistant schizophrenia (TRS). This subgroup faces remarkable medical and psychosocial damages, and pharmacotherapy is often limited due to nonresponse and/or side effects. Maintenance electroconvulsive therapy (M-ECT) might be effective in TRS. Patient concerns: We present a case of a 26-year-old male patient with a TRS. Diagnoses: He received a treatment series of ECT sessions and a course of 24 M-ECTs. Interventions: The entire treatment was tolerated without significant side effects. Outcomes: Moreover, the Psychotic Symptom Rating Scale (PSYRATS) scores for both positive and negative symptoms decreased and remained stable over the course of M-ECT. Lessons: Because of the remarkable improvement in the negative and positive symptom clusters, we propose systematic examinations in the field of M-ECT in TRS patients. These studies should integrate long-term outcome and tolerance measurements, gaining insight into the optimal duration of treatment for this indication.